Nutrition Mass of Fermented Coconut Pulp with Rumen Fluid as Poultry Feed - Irmayanti, Irmayanti; Mahanani, Agni Ayudha; Said, Nur Saidah; Sarman, Aco Parawansa; Suardi, Suardi (Jurnal Peternakan, 2024)
The use of coconut pulp as animal feed is still limited due to the high content of crude fat and crude fiber, which are difficult to digest by livestock and low palatability, so feed processing technology is needed, one of which is through the fermentation process with the addition of microorganisms from rumen fluid. This study aimed  to determine the nutritional quality of coconut (Cocos nucifera l.) pulp with different fermentation lengths using Bali cow rumen fluid.  The study used a completely randomized design (CRD) consisting of 3 treatments and 4 replicates. The treatments used in this study were AA = 0-day coconut pulp (control), AB = 5-day fermented coconut pulp, and A2 = 7-day fermented coconut pulp. The variables observed were dry matter (DM), crude protein (CP), crude fiber (CF), and crude fat (FF). The results showed a significant effect (P<0.05) on the mean values of BK AA (94.669±0.33) AB (91.89±0.23) and AC (90.46±0.44), PK AA (5.33±0.41), AB (6.00±0.14) and AC (6.59±0. 15), SK AA (16.99±0.31), AB (10.16±0.21), and AC (9.24±0.24) and showed no significant effect (P>0.05) on the mean value of LK AA (44.55±0.50), AB (44.52±0.3), and AC (43.29±0.58). Based on the results of the study, it was concluded that 7-day fermentation decreased BK, LK, and SK and increased PK of coconut pulp.  The best fermentation time of coconut pulp with Bali cow rumen fluid is on day 7.